EVALUASI SISTEM E-SAMSAT BERBASIS MOBILE UNTUK LAYANAN MASYARAKAT KOTA PALEMBANG DENGAN TECHNOLOGY ACCEPTANCE MODEL - Tujni, Baibul ; Hutrianto, Hutrianto (Universitas Bina Darma, 2018)
The development of science and information technology supports activities carried out by individuals in using technology, to support operational and management performance. Such as Mobile-based e-Samsat Service to serve vehicle taxation with two-wheeled or four-wheeled vehicles, especially the people of Palembang. Mobile tax payments that can make it easier and closer to densely populated locations or caused by busyness. Information systems help service income tax factors of successful application and use of information technology are user factors. The level of readiness of users to receive information technology has a major influence in determining whether or not the application of the technology is successful. The purpose of this study is to identify factors that influence users in using the mobile-based e-Samsat Information System in the city of Palembang. Data analysis was carried out with SPSS (Statistical package for the social science) with the TAM (Technology Acceptance Model) software which is a technology acceptance model that will be used by technology users. By evaluating e-Samsat, it is to find out whether the system has served motor vehicle tax payments properly and has met service quality standards. This study will evaluate the performance of e-Samsat with TAM instruments Keywords: evaluation, convenience, benefits / uses, e-Samsat, Tam, SPSS